129k views
1 vote
Factor this equation , I can’t comprehend it

Factor this equation , I can’t comprehend it-example-1
User Wilson
by
4.8k points

2 Answers

5 votes

Answer:

B

Explanation:

using the method of difference of 2 squares

• a² - b² = (a + b)(a - b)

For 4x² - 9

with 4x² = (2x)² ⇒ a = 2x

9 = 3² ⇒ b = 3

4x² - 9 = (2x + 3)(2x - 3) → B


User ITwenty
by
4.7k points
3 votes

Answer:

B) (2x + 3)(2x - 3)

Explanation:

Use the FOIL method for each answer choice.

FOIL = First, Outside, Inside, Last

(2x)(2x) = 4x²

(2x)(-3) = -6x

(3)(2x) = 6x

(3)(-3) = -9

4x² -6x +6x -9

Simplify. Combine like terms:

4x² (-6x + 6x) - 9

4x² - 9

4x² - 9 = 4x² - 9 ∴ B) (2x + 3)(2x - 3) is your answer

~

User Horst
by
4.7k points